Material didático contextualizado na astronomia para contribuir na melhoria de habilidades matemáticas dos estudantes do ensino médio em física e matemática - Cordeiro, James Cloy Leite (2017)
This research aims to implement the didactic sequence as a teaching strategy that can enable the improvement of mathematical skills in Mathematics’ and Physics’ classes, contextualized in Astronomy. The research question was guided by the following question: What are the contributions of the Didactic Sequence in the improvement of students' mathematical abilities, using concepts of physics and mathematics contextualized in Astronomy? Thus, this research is configured as applied research, anchored in the principles of the qualitative approach. For that, we developed and analyzed Didactic Sequences, which were elaborated based on the Guidelines of the National Curricular Parameters on the Universe, Earth and Life theme, on suggestions of activities of the Brazilian Astronomy Olympiad (OBA) based on the theory of Significant Critical Learning. The subjects involved in the process were the High School Students of the Assis Chateaubriand Integrated Education Center (CIEAC). It was a relevant study that sought to use students' experiences and knowledge, from a reflexive listening. This enabled me to perceive that a pedagogical practice, which considers the subjects of the process, contributes to a motivating learning exercise. In the case of Mathematics’ and Physics’ teaching, it helps to improve the mathematical skills of high school students, using concepts contextualized in Astronomy.